Influence of intentional ankylosis of deciduous canines to reinforce the anchorage for maxillary protraction - Luís Fernando Castaldi Tocci; Omar Gabriel da Silva Filho; Acácio Fuziy; José Roberto Pereira Lauris (Dental Press Editora, 2013)
INTRODUCTION: This retrospective cephalometric study analyzed the influence of intentional ankylosis of deciduous canines in patients with Class III malocclusion and anterior crossbite, in the deciduous and early mixed dentition stages, treated by orthopedic maxillary expansion followed by maxillary protraction. METHODS: Lateral cephalograms of 40 patients were used, divided in 2 groups paired for age and gender. The Ankylosis Group was composed of 20 patients (10 boys and 10 girls) treated with induced ankylosis and presenting initial and final mean ages of 7 years 4 months and 8 years 3 months, respectively, with a mean period of maxillary protraction of 11 months. The Control Group comprised 20 patients (10 boys and 10 girls) treated without induced ankylosis, with initial and final mean ages of 7 years 8 months and 8 years 7 months, respectively, with a mean period of maxillary protraction of 11 months. Two-way analysis of variance and covariance analysis were applied to compare the initial and final cephalometric variables and the treatment changes between groups. RESULTS: According to the results, the variables evidencing the significant treatment changes between groups confirmed that the intentional ankylosis enhanced the sagittal response of the apical bases (Pg-NPerp) and increased the facial convexity angles (NAP and ANB). CONCLUSIONS: The protocol involving intentional ankylosis of deciduous canines enhanced the sagittal response of the apical bases. INTRODUÇÃO: nesse estudo cefalométrico retrospectivo, analisou-se a influência da anquilose intencional de caninos decíduos em pacientes com má oclusão de Classe III e mordida cruzada anterior, nos estágios de dentição decídua e mista precoce, tratados com expansão ortopédica da maxila, seguida de tração reversa. MÉTODOS: foram utilizadas telerradiografias em norma lateral de 40 pacientes, divididos em 2 grupos pareados por idade e sexo. O Grupo Anquilose foi constituído de 20 pacientes (10 meninos e 10 meninas) tratados com anquilose induzida e que apresentavam as idades médias inicial e final, respectivamente, de 7a 4m e 8a 3m, e o tempo médio de tração reversa de 11 meses. O Grupo Controle, composto de 20 pacientes (10 meninos e 10 meninas) tratados sem anquilose induzida e que apresentavam as idades médias inicial de 7a 8m e final de 8a 7m, e tempo médio de tração reversa de 11 meses. Foram empregadas as análises de Variância a dois critérios e de Covariância para comparar as variáveis cefalométricas inicial e final e as alterações de tratamento entre os grupos. RESULTADOS: segundo os resultados, as variáveis que evidenciaram as mudanças de tratamento significativas entre os grupos confirmaram que o procedimento de anquilose intencional potencializou a resposta sagital das bases apicais (Pg-NPerp) e aumentou os ângulos de convexidade facial (NAP e ANB). CONCLUSÃO: o protocolo envolvendo a anquilose intencional de caninos decíduos potencializou a resposta sagital das bases apicais.